Read. This. Slowly: mimicking spoken pauses in text messages - Poirier, Rachel C.; Cook, Andrew M.; Klin, Celia M. (Frontiers in Psychology, 2025)
In contrast with face-to-face conversations, text messages lack important extralinguistic cues such as tone of voice and gestures. We ask how texters are able to communicate the same nuanced social and emotional meaning without access to this rich set of multimodal cues. The current paper expands on previous work examining the role of one particular textism, the period, and found that the inclusion of a period after a single-word text (yup.) could convey abruptness, or insincerity. Across three experiments, we used a rating scale to examine two additional textisms and found that the inclusion of a period after each word in an exchange (No. Just. Go) as well as breaking the exchange into a series of single-word texts ([no] [just] [go]) conveyed emotions such as disgust and frustration. These textisms may have mimicked prosody, influencing readers’ understanding of the emotionality of the message. More generally, the results demonstrate that texters make use of a variety of textisms to communicate social and emotional information.